Voice assistant for web applications - Nesmiian, D. (ХНУРЕ, 2023)
The current work is dedicated to comparing user interaction algorithms with web interfaces of web applications using voice, particularly in educational platforms. The main principles of voice technology operation at different levels of hardware and software systems are considered. A comparison of the most popular voice assistants and the technologies used to create them has been conducted. It has been determined that optimizing additional functionality for controlling a web page using voice improves the user experience and contributes to user’s return to the web application